Tea Growing and Socio-Economic Wellbeing of the Community of Kyamuhunga-Bushenyi. - Nuwasiima, Olivia (Kabale University, 2024)
This research investigated the socio-economic impact of tea growing on the community of Kyamuhunga, Bushenyi District, Uganda. Despite the significant role of tea cultivation in the livelihoods of households in Kyamuhunga, there is a lack of comprehensive understanding of its implications for community development. Through a mixed-methods approach, including quantitative surveys, qualitative interviews, and participatory research techniques, this study aims to address this knowledge gap by examining various aspects of tea cultivation and its socio-economic effects on the local community. The research has assessed the contribution of tea growing to household incomes, livelihood diversification, and poverty alleviation within Kyamuhunga. It also analyzed the employment generation potential of tea cultivation, including labor dynamics, job creation, and opportunities for youth and women empowerment. Additionally, the study explored the social dynamics of tea cultivation, including its impact on community cohesion, gender roles, and cultural practices. Environmental implications, such as land use changes, soil erosion, and water pollution, were also examined. Furthermore, the research evaluated existing policies, regulations, and institutional frameworks governing tea production and trade in Kyamuhunga. It identified challenges faced by tea growers and the community, as well as opportunities for innovation, value addition, and market diversification. Ultimately, the findings of this research aim to inform evidence-based policies and interventions for maximizing the positive socio-economic impacts of tea cultivation while mitigating potential challenges, thus contributing to sustainable community development in Kyamuhunga, Bushenyi District, and beyond.